Agricultural Communications: Perspectives from the Experts - Fawn Kurtzo; Maggie Jo Hansen; K. Jill Rucker; Leslie D. Edgar (Journal of Applied Communications, 2016)
This qualitative research study evaluates the perspectives of agricultural communications (ACOM) according to ACOM experts (N = 25) from across the United States. Respondents represented policy makers, industry leaders, educators, and researchers and averaged about 15 years of experience. However, respondents were unable to identify a consistent definition of ACOM. Skills and characteristics needed by agricultural communicators ranged from general agriculture and policy understanding to technical communications and science knowledge. Audience identification, agricultural and policy knowledge, and targeted message development and delivery were all important skills needed by ACOMRs. Agricultural communicator characteristics focused on being flexible, responsible, gaining trust, and thinking critically. Challenges, sometimes noted as barriers, ranged from knowledge area changes to division and defense and from a non-unified voice to rapid expansion of technology. The discussion of higher education institutions training generalists versus specialists is an important topic based on findings of this study. Recommendations for future ACOM focus and education are discussed.
Keywords: Agricultural Communications; Influencing Factors; Future Directions; History